2013
DOI: 10.1186/1478-4491-11-4
|View full text |Cite
|
Sign up to set email alerts
|

E-learning in medical education in resource constrained low- and middle-income countries

Abstract: BackgroundIn the face of severe faculty shortages in resource-constrained countries, medical schools look to e-learning for improved access to medical education. This paper summarizes the literature on e-learning in low- and middle-income countries (LMIC), and presents the spectrum of tools and strategies used.MethodsResearchers reviewed literature using terms related to e-learning and pre-service education of health professionals in LMIC. Search terms were connected using the Boolean Operators “AND” and “OR” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
417
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(460 citation statements)
references
References 41 publications
4
417
0
8
Order By: Relevance
“…12 William stated that paramedical students also found computer-based learning to be useful for their learning; however, not all the students can accept the application of computer-based learning in the online environment as some of them are facing difficulties in accessing the internet other than in their university. 17 In Malaysia, there are also studies of e-learning intervention done on health science faculties including the biomedical science, optometry, and nutrition and dietetics department.…”
Section: E-learning Practice In Health Science Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…12 William stated that paramedical students also found computer-based learning to be useful for their learning; however, not all the students can accept the application of computer-based learning in the online environment as some of them are facing difficulties in accessing the internet other than in their university. 17 In Malaysia, there are also studies of e-learning intervention done on health science faculties including the biomedical science, optometry, and nutrition and dietetics department.…”
Section: E-learning Practice In Health Science Educationmentioning
confidence: 99%
“…Although a number of studies have been done in tertiary education related to e-learning, not many studies focus on specific departments such as health science department. 2,3,[9][10][11][12][13][14][15][16][17] By doing the microscopic study of e-learning in specific departments such as in pharmacy education, generalizing the findings from the study is not allowed as it is only the fraction of the interested population. However, by understanding the students' perception on e-learning in a small scale, earlier modification can be made by the lecturers and academic staff as to motivate and overcome any problems faced by the students.…”
Section: Introductionmentioning
confidence: 99%
“…Boolean Operators "AND" and "OR" were used to connect search terms aimed to study all relevant article suggestions [12].…”
Section: Methodsmentioning
confidence: 99%
“…Frehywot et al [12] carried out the research on e-learning in medical education in resource constrained countries and found that low quality of videos or visual outputs was one of the major challenge users were facing, due to bandwidth limitations that often contributed to low speed network. Therefore, designers of learning content must follow good learning theories and appropriate instructional design for the learning to be effective.…”
mentioning
confidence: 99%
“…Potential tools, techniques and procedures that can aid education and training in resource limited environments include: (1) e-learning [68][69][70][71] , (2) e-mentoring/e-rounds 72 (e.g., http://chartrounds.com/), (3) collaborative course development/education/training 39,73 , and (4) courses provided by national/international organizations 74 .…”
Section: Educational Infrastructurementioning
confidence: 99%